Preparation method of anti-aging cellulose insulation paper

By sieve the fine fibers in cellulose insulating paper and use aramid nanofibers instead, combined with wet molding and calendering processes, aging-resistant cellulose insulating paper is prepared, which solves the problem of degradation of insulation performance and mechanical strength of cellulose insulating paper in long-term use, extends service life and improves aging resistance.

CN119593257AActive Publication Date: 2025-03-11TIANJIN UNIV OF SCI & TECH

Patent Information

Application Number
CN202411847883.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-11
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

Existing cellulose insulating paper is prone to deterioration in insulation performance and mechanical strength during long-term use, which makes it difficult for oil-immersed transformers to run for a long time and the aging process is irreversible.

Method used

The fine fibers in the pulp are screened, aramid nanofibers are used instead, long fibers are retained, and cellulose insulated paper is prepared by wet molding and calendering processes to reduce the rate of polymerization drop and improve breakdown strength.

Benefits of technology

It extends the service life of cellulose insulated paper, improves its aging resistance in high-voltage environments, and ensures long-term safe operation of ultra-high voltage transformers and high-quality power supply.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of anti-aging cellulose insulation paper, and belongs to the technical field of oil paper insulation for electrical equipment. The problems that in the prior art, the polymerization degree of cellulose insulation paper in an oil-paper insulation system is greatly reduced, so that aging is caused, the insulation performance is reduced, and the service life is shortened are solved. The preparation method comprises the following steps: firstly, pre-treating natural color softwood pulp, grinding the softwood pulp to different degrees, and mixing the softwood pulp; secondly, purifying the mixed paper pulp, screening out fine fibers, and replacing the screened-out fine fibers with aramid nanofibers to prepare mixed paper pulp containing the aramid nanofibers; adding the mixed paper pulp containing the aramid nanofibers into a sheet making machine, performing dehydration forming and drying to obtain raw paper, and performing calendaring to obtain the cellulose insulation paper. The aging resistance and the insulating property of the cellulose insulating paper are remarkably improved, and the performance requirements of the insulating paper for the ultra-high voltage transformer can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the cross-technical field of papermaking industry and material industry, and particularly relates to a method for preparing cellulose insulating paper used for an ultra-high voltage transformer. Background Art

[0002] There are many types of transformers in my country. According to the transformer cooling method, transformers can be divided into self-cooling and evaporative cooling types. Self-cooling transformers include oil-immersed transformers and dry-type transformers, and evaporative cooling transformers include chlorinated fluorine transformers. Among the three types of transformers, oil-immersed transformers are the most traditional transformers. They account for the highest proportion of transformers in operation and have the widest application range. Their insulation system mainly adopts an "oil-paper" composite system consisting of mineral oil and cellulose insulating paper or paperboard. The insulating oil and cellulose insulating paper in the composite system will age during use, that is, they will degrade under the action of electricity, thermal stress, oxygen and moisture. This process is called aging. The insulation and mechanical properties of cellulose insulating paper will gradually decrease during the aging process. However, according to actual operating experience, even after long-term use, the insulation breakdown voltage of insulating oil is only reduced by about 10%, which generally does not hinder operation or can be solved by oil purification or regeneration or even replacement of new oil, so it is not the main factor affecting the life of the transformer. Cellulose insulation paper is a solid material. It plays an insulating electric field role on each winding by winding. After aging, it cannot be replaced during the operation of the transformer. Therefore, the life of the oil-immersed transformer depends on the life of the cellulose insulation paper. With the development of the power industry, the transmission voltage level of the power grid continues to increase. Cellulose insulation paper is prone to degradation of insulation performance and mechanical strength during long-term use, which directly leads to a significant decrease in the degree of polymerization of cellulose insulation paper, making it difficult for oil-immersed transformers to operate for a long time. The degree of polymerization is one of the characteristic quantities of cellulose insulation paper aging phenomenon. The average degree of polymerization of cellulose insulation paper is about 1000-1300. When the degree of polymerization drops to 500, it is considered that the insulation system of the transformer has entered the middle of its life; when the degree of polymerization drops to 250, it is considered that the insulation system of the transformer has reached the end of its life. In the "oil-paper" composite system, with the increase of operating time, cellulose insulation paper gradually ages under the influence of various aging factors, and the aging process is irreversible. After cellulose insulation paper is soaked in oil, the fine fibers in it are the first to degrade, which is manifested as brittleness of the paper on a macroscopic level and the breakage of glycosidic bonds on a microscopic level. The breakage of fine fibers will generate more water. Under the combined effect of water generation and other factors, the polymerization degree of the paper is directly reduced, which eventually leads to the degradation of electrical and mechanical properties and breakdown, and the life of the insulation paper is severely shortened. When the polymerization degree of cellulose insulation paper drops below 250, the cellulose insulation paper in the "oil-paper" composite system needs to be replaced, otherwise it will cause a series of serious insulation failures and even lead to accidents.

[0003] Therefore, it is imperative to develop aging-resistant cellulose insulation paper, and nanotechnology may be a promising solution. Liao Ruijin et al. added nano-Al with low relative dielectric constant to cellulose insulation paper. 2 O 3 The particles improve the DC breakdown strength of nano-modified cellulose insulation paper. Tang Chao et al. added nano-TiO 2 Or nano-montmorillonite improves the AC breakdown strength of cellulose insulation paper. The results show that when nano-TiO 2 The content is 3wt% or when the nano Al 2 O 3 When the particle content is 1wt%, the AC and DC breakdown strength of nanoparticle-modified cellulose insulation paper is the highest and the insulation performance is the best. However, the disadvantages of inorganic nanoparticle-modified cellulose insulation paper are also obvious. First, there are differences in density and hydrophilicity between nanoparticles and natural fibers. Nanoparticles cannot be evenly dispersed in natural fibers, and nanoparticles will agglomerate on the surface and inside of the fibers. Second, the size of nanoparticles is small, and it is very easy for them to flow away with the addition of slurry during the papermaking process, making it difficult to form a paper structure on the filter screen. The retention rate is a difficult problem that needs to be overcome. The above two points will directly lead to a decrease in the mechanical properties and insulation properties of cellulose insulation paper, which cannot meet the requirements of cellulose insulation paper for ultra-high voltage transformers.

[0004] In recent years, aramid nanofibers have gradually become a research hotspot for aging-resistant cellulose insulation paper for electronic and power systems due to their outstanding mechanical properties, thermal stability, and insulation properties. This organic synthetic material is known for its extremely high strength and modulus, low density, and excellent wear resistance. Its chemical structure is stable, similar to that of natural fibers, and can be more effectively combined with natural fibers. The large aspect ratio of aramid nanofibers is conducive to the construction of a network structure in natural fibers, which effectively solves the problem of the difficulty in uniform distribution and poor retention of nanoparticles in cellulose insulation paper. This study proposes a method for modifying cellulose insulation paper using aramid nanofibers. The method uses unbleached kraft softwood pulp as raw material, removes the fine fibers therein, and selects long fibers that degrade more slowly during the aging process. These long fibers are mixed with aramid nanofibers to prepare cellulose insulation paper with good mechanical properties and excellent insulation properties. Summary of the invention

[0005] During the operation of the ultra-high voltage transformer, the cellulose insulating paper will gradually age due to the influence of factors such as temperature, electric field, moisture, and oxygen, resulting in a serious decline in the insulation performance of the ultra-high voltage transformer, which greatly shortens the life of the ultra-high voltage transformer. In view of this shortcoming, the present invention provides a method for preparing aging-resistant cellulose insulating paper, by screening out fine fibers in the pulp, replacing the screened fine fibers with aramid nanofibers, and retaining long fibers, that is, the insulating paper uses long fibers that degrade more slowly during the operation of the transformer for pulping and papermaking. After mechanical treatment, the rate of decrease in the degree of polymerization of the cellulose insulating paper can be reduced, and its breakdown strength can be improved. After being soaked in oil, the cellulose insulating paper has great "endurance" and does not pollute the environment, so that it can meet the requirements of long-term safe operation, high-quality, and stable power supply of ultra-high voltage transformers.

[0006] The technical solution adopted by the present invention is:

[0007] A method for preparing aging-resistant cellulose insulating paper, characterized in that it comprises the following steps:

[0008] (1) Pre-treating the wood pulp board: soaking the wood pulp board in deionized water to loosen it;

[0009] (2) subjecting the pretreated pulp to mechanical refining to different degrees, and mixing the pulp in proportion according to the difference in the degree of beating to obtain a mixed pulp;

[0010] (3) subjecting the mixed slurry to purification treatments: hydrochloric acid treatment and magnesium acetate treatment;

[0011] (4) mechanically screening the treated pulp to remove fine fibers in the pulp and obtain a good pulp free of fine fibers;

[0012] (5) replacing the cellulose fine component with an equal amount of aramid nanofibers to obtain a mixed pulp containing aramid nanofibers;

[0013] (6) debonding the obtained mixed pulp and obtaining cellulose base paper by wet forming technology;

[0014] (7) The obtained cellulose base paper is calendered to obtain cellulose insulating paper.

[0015] Preferably, the wood pulp board is an unbleached kraft coniferous wood board with a degree of polymerization of 1500 to 1800.

[0016] Preferably, the refining speed of the mechanical refining is 8000-15000r, the refining slurry concentration is 8-10%, the refining gap is 0-2mm, and the beating degree is 45-85°SR.

[0017] Preferably, the mixed slurry is mixed according to the degree of beating, wherein the low beating degree ranges from 45 to 65°SR, the high beating degree ranges from 80 to 85°SR, and the mixing ratio of the two is 6:4 to 8:2.

[0018] Preferably, the acid treatment slurry concentration is 3-5%, and the hydrochloric acid concentration is 1-2%; the magnesium salt treatment slurry concentration is 1-3%, and the magnesium acetate concentration is 2-4%.

[0019] Preferably, the mechanical screening is screening by a Ball sieving instrument, and the slurry retained by the sieve with a mesh size of 30 to 100 is taken.

[0020] Preferably, the nanofiber is aramid nanofiber (ANF) with a diameter of 120-140 nm and an aspect ratio of 800-1000.

[0021] Preferably, the content of the replaced fine fibers is 5-15% of the mass of the cellulose insulation paper, that is, the content of the nanofibers is 6-18% of the mass of the finished paper.

[0022] Preferably, the roller calendering temperature is 70-80° C., the hot pressing roller speed is 1-3 m / min, and the calendering line pressure is 30-40 N / mm.

[0023] Beneficial effects:

[0024] (1) As the operation time of the ultra-high voltage transformer increases, the long fibers, short fibers and fine fibers in the cellulose insulating paper of the "oil-paper" composite system will degrade first under the action of various factors, followed by the short fibers. The cleavage of the glycosidic bonds on the fine fibers will generate more free water, which will directly lead to a decrease in the length of the cellulose chain and a decrease in the polymerization degree of the long fibers, and ultimately lead to a decrease in the mechanical properties of the cellulose insulating paper. The cellulose insulating paper will be broken down during use, and its life will be shortened, which will cause the ultra-high voltage transformer to malfunction or even a serious accident. The purpose of screening pulp in the present invention is to select pulp fractions with better chemical pulp performance, select long fibers intercepted by the screen, replace the screened fine fibers with aramid nanofibers, mix the two, and prepare cellulose insulating paper containing aramid nanofibers. The participation of aramid nanofibers improves the electrical properties of cellulose insulating paper, effectively slows down the degradation rate of the pulp polymerization degree during the aging process, and to a certain extent prolongs the life of the insulating paper, making the cellulose insulating paper more resistant to aging during long-term operation.

[0025] (2) The present invention uses wet papermaking technology to make cellulose insulating paper, and the screening of fine fibers in the pulp will slightly reduce the mechanical and electrical properties of the cellulose insulating paper. Aramid nanofibers, with their high strength and high modulus characteristics, have a certain strengthening effect on the strength properties of paper. This strengthening effect is crucial for cellulose insulating paper to resist the performance degradation caused by mechanical stress during aging. Therefore, by replacing the screened fine fibers with aramid nanofibers and further treating the base paper containing aramid nanofibers in the subsequent calendering process, the close connection between the fibers can be promoted. This process ensures the good mechanical properties of the cellulose insulating paper; in addition, due to the presence of aramid nanofibers in the "oil-paper" composite system, the rate of decrease in the degree of polymerization of the cellulose insulating paper during the operation of the ultra-high voltage transformer is slowed down, thereby extending the service life of the transformer. Specific implementation plan

[0026] The present invention is described in detail below in conjunction with specific implementation modes.

[0027] Example 1

[0028] Take 360g of natural softwood pulp board and soak it in deionized water for 4 hours, tear it into small pulp pieces of 25mm×25mm; pour the pulp pieces into a Wall-E pulper and add deionized water to make the pulp concentration reach 2.5%, disperse until there are no small pulp pieces, squeeze out the water and proceed to the next step of pulping treatment;

[0029] Take 30g of the pretreated slurry, add deionized water to a total weight of 300g, and place it in a PFI beater for beating at a beating speed of 8000r and a beating degree of 45°SR. Take another 30g of the pretreated slurry, add deionized water to 300g, and place it in a PFI beater for beating at a beating speed of 15000r and a beating degree of 85°SR. Mix the two in a mass ratio of 6:4, dehydrate the mixed slurry and set aside;

[0030] Take 30g of the mixed slurry, adjust the slurry concentration to 4%, add 3mL of 3wt% hydrochloric acid, stir evenly, and treat for 60min; wash three times with deionized water after acid treatment, each treatment time is 5min; adjust the slurry concentration after washing to 4%, add 1.5g of magnesium acetate, stir evenly, and treat for 60min. Wash three times with deionized water after magnesium salt treatment, each treatment time is 5min. Dehydrate, break up, and balance the water content of the washed slurry to obtain the treated slurry;

[0031] Take 15g of the treated mixed slurry and use a Bauer sieving instrument to sieve, and preferably take the slurry with a mesh size of 30 mesh. The sieving time is 30min, and the process is repeated 24 times. Let it stand for 4h to balance the moisture;

[0032] Weigh 0.4 g of aramid nanofibers (accounting for 16.85% of the mass of the base paper) to replace fine fibers, and mix the aramid nanofibers with the preferred slurry;

[0033] The treated slurry was debonded at a speed of 10,000 r. The obtained suspension was added to a sheet making machine for dehydration and molding to prepare a 75 g / m 2 The wet paper sheet was dried at 95°C for 10 min to obtain cellulose base paper;

[0034] The obtained cellulose base paper was calendered at a calendering temperature of 70° C., a hot pressing roller speed of 1 m / min, and a pressure of 30 N / mm to obtain cellulose insulating paper.

[0035] The performance parameters of the cellulose insulation paper prepared in Example 1 are as follows: the ash content of the paper is 0.23% (≤0.25%), the sodium ion content in the ash is 23.3 mg·kg -1 (≤30mg·kg -1 ), thickness is 78μm, tensile strength is 6.39kN / m, tear strength is 1307mN, folding endurance is 1017 times, breakdown voltage is 1.29kV, breakdown strength is 13.43kV / mm; the degree of polymerization of cellulose insulation paper impregnated with oil at 0d (day) is 1089, and the degree of polymerization of cellulose insulation paper impregnated with oil at 25d is 263; the breakdown strength of cellulose insulation paper impregnated with oil at 0d is 18.0kV / mm, and the breakdown strength of cellulose insulation paper impregnated with oil at 25d is 10.42kV / mm.

[0036] Example 2

[0037] Take 360g of natural softwood pulp board and soak it in deionized water for 4 hours, tear it into small pulp pieces of 25mm×25mm; pour the pulp pieces into a Wall-E pulper and add deionized water to make the pulp concentration reach 2.5%, disperse until there are no small pulp pieces, squeeze out the water and proceed to the next step of pulping treatment;

[0038] Take 30g of the pretreated slurry, add deionized water to a total weight of 300g, and place it in a PFI beater for beating at a beating speed of 8500r and a beating degree of 55°SR. Take another 30g of the pretreated slurry, add deionized water to 300g, and place it in a disc mill for beating at a beating speed of 15000r and a beating degree of 85°SR. Mix the two at a mass ratio of 6:4, dehydrate the mixed slurry and set aside;

[0039] Take 30g of the mixed slurry, adjust the slurry concentration to 4%, add 3mL of 3wt% hydrochloric acid, stir evenly, and treat for 60min; wash three times with deionized water after acid treatment, each treatment time is 5min; adjust the slurry concentration after washing to 4%, add 1.5g of magnesium acetate, stir evenly, and treat for 60min. Wash three times with deionized water after magnesium salt treatment, each treatment time is 5min. Dehydrate, break up, and balance the water content of the washed slurry to obtain the treated slurry;

[0040] Take 15g of the treated mixed slurry and use a Bauer sieving instrument to sieve, and take the slurry that is intercepted by both 30 mesh and 100 mesh. The sieving time is 30min, and the process is repeated 24 times. Let it stand for 4h to balance the moisture;

[0041] Weigh 0.3 g of aramid nanofibers (accounting for 12.62% of the mass of the base paper) to replace the fine fibers, and mix the aramid nanofibers with the preferred slurry;

[0042] The treated slurry was debonded at a speed of 10,000 r. The obtained suspension was added to a sheet making machine for dehydration and molding to prepare a 75 g / m 2 The wet paper sheet was dried at 95°C for 10 min to obtain cellulose base paper;

[0043] The obtained cellulose base paper was calendered at a calendering temperature of 80° C., a hot pressing roller speed of 1 m / min, and a pressure of 3 N / mm to obtain cellulose insulating paper.

[0044] The performance parameters of the cellulose insulation paper prepared in Example 2 are as follows: the ash content of the paper is 0.24% (≤0.25%), the sodium ion content in the ash is 23.4 mg·kg -1 (≤30mg·kg -1 ), thickness is 78μm, tensile strength is 6.38KN / m, tear strength is 1309mN, folding endurance is 1019 times, breakdown voltage is 1.28kV, breakdown strength is 13.38kV / mm; the degree of polymerization of cellulose insulation paper impregnated with oil at 0d is 1091, and the degree of polymerization of cellulose insulation paper impregnated with oil at 25d is 261; the breakdown strength of cellulose insulation paper impregnated with oil at 0d is 17.87kV / mm, and the breakdown strength of cellulose insulation paper impregnated with oil at 25d is 10.12kV / mm.

[0045] Example 3

[0046] Take 360g of natural softwood pulp board and soak it in deionized water for 4 hours, tear it into small pulp pieces of 25mm×25mm; pour the pulp pieces into a Wall-E pulper and add deionized water to make the pulp concentration reach 2.5%, disperse until there are no small pulp pieces, squeeze out the water and proceed to the next step of pulping treatment;

[0047] Take 30g of the pretreated slurry, add deionized water to a total weight of 300g, and place it in a PFI beater for beating at a beating speed of 9000r and a beating degree of 65°SR. Take another 30g of the pretreated slurry, add deionized water to 300g, and place it in a PFI beater for beating at a beating speed of 15000r and a beating degree of 85°SR. Mix the two at a mass ratio of 8:2, dehydrate the mixed slurry and set aside;

[0048] Take 30g of the mixed slurry, adjust the slurry concentration to 4%, add 3mL of 3wt% hydrochloric acid, stir evenly, and treat for 60min; wash three times with deionized water after acid treatment, each treatment time is 5min; adjust the slurry concentration after washing to 4%, add 1.5g of magnesium acetate, stir evenly, and treat for 60min. Wash three times with deionized water after magnesium salt treatment, each treatment time is 5min. Dehydrate, break up, and balance the water content of the washed slurry to obtain the treated slurry;

[0049] Take 15g of the treated mixed slurry and use a Bauer sieving instrument to sieve it. The slurry with a mesh size of 30 mesh and 50 mesh is preferably selected. The sieving time is 30min. Repeat this process 24 times and let it stand for 4h to balance the moisture.

[0050] Weigh 0.16 g (accounting for 6.88% of the mass of the base paper) of aramid nanofibers to replace fine fibers, and mix the aramid nanofibers with the preferred slurry;

[0051] The treated slurry was debonded at a speed of 10,000 r. The obtained suspension was added to a sheet making machine for dehydration and molding to prepare a 75 g / m 2 The wet paper sheet was dried at 95°C for 10 min to obtain cellulose base paper;

[0052] The obtained cellulose base paper was calendered at a calendering temperature of 75° C., a hot pressing roller speed of 1 m / min, and a pressure of 35 N / mm to obtain cellulose insulating paper.

[0053] The performance parameters of the cellulose insulation paper prepared in Example 3 are as follows: the ash content of the paper is 0.22% (≤0.25%), the sodium ion content in the ash is 22.6 mg·kg -1 (≤30mg·kg -1), thickness is 78μm, tensile strength is 6.56kN / m, tear strength is 1217mN, folding endurance is 1085 times, breakdown voltage is 1.25kV, breakdown strength is 13.37kV / mm; the degree of polymerization of cellulose insulation paper impregnated with oil at 0d is 1109, and the degree of polymerization of cellulose insulation paper impregnated with oil at 25d is 268; the breakdown strength of cellulose insulation paper impregnated with oil at 0d is 17.56kV / mm, and the breakdown strength of cellulose insulation paper impregnated with oil at 25d is 10.13kV / mm.

[0054] Example 4

[0055] Take 360g of natural softwood pulp board and soak it in deionized water for 4 hours, tear it into small pulp pieces of 25mm×25mm; pour the pulp pieces into a Wall-E pulper and add deionized water to make the pulp concentration reach 2.5%, disperse until there are no small pulp pieces, squeeze out the water and proceed to the next step of pulping treatment;

[0056] Take 30g of the pretreated pulp, add deionized water to a total weight of 300g, and place it in a PFI beater for beating at a beating speed of 8500r and a beating degree of 55°SR. Take another 30g of the pretreated pulp, add deionized water to 300g, and place it in a disc mill beater for beating at a beating speed of 15000r and a beating degree of 85°SR. Mix the two at a mass ratio of 8:2, dehydrate the mixed pulp and set aside;

[0057] Take 30g of the mixed slurry, adjust the slurry concentration to 4%, add 3mL of 3wt% hydrochloric acid, stir evenly, and treat for 60min; wash three times with deionized water after acid treatment, each treatment time is 5min; adjust the slurry concentration after washing to 4%, add 1.5g of magnesium acetate, stir evenly, and treat for 60min. Wash three times with deionized water after magnesium salt treatment, each treatment time is 5min. Dehydrate, break up, and balance the water content of the washed slurry to obtain the treated slurry;

[0058] Take 15g of the treated mixed slurry and use a Bauer sieving instrument to sieve it. The slurry with a mesh size of 30 mesh and 50 mesh is preferably selected. The sieving time is 30min. Repeat this process 24 times and let it stand for 4h to balance the moisture.

[0059] Weigh 0.16 g (accounting for 6.88% of the dry weight of the base paper) of aramid nanofibers to replace fine fibers, and mix the aramid nanofibers with the preferred slurry;

[0060] The treated slurry was debonded at a speed of 10,000 r. The obtained suspension was added to a sheet making machine for dehydration and molding to prepare a 75 g / m 2 The wet paper sheet was dried at 95°C for 10 min to obtain cellulose base paper;

[0061] The obtained cellulose base paper was calendered at a calendering temperature of 75° C., a hot pressing roller speed of 1 m / min, and a pressure of 40 N / mm to obtain cellulose insulating paper.

[0062] The performance parameters of the cellulose insulation paper prepared in Example 4 are as follows: the ash content of the paper is 0.25% (≤0.25%), the sodium ion content in the ash is 23.8 mg·kg -1 (≤30mg·kg -1 ), thickness is 78μm, tensile strength is 6.32kN / m, tear strength is 1295mN, folding endurance is 1094 times, breakdown voltage is 1.36kV, breakdown strength is 13.91kV / mm; the degree of polymerization of cellulose insulation paper impregnated with oil at 0d is 1017, and the degree of polymerization of cellulose insulation paper impregnated with oil at 25d is 269; the breakdown strength of cellulose insulation paper impregnated with oil at 0d is 18.07kV / mm, and the breakdown strength of cellulose insulation paper impregnated with oil at 25d is 10.06kV / mm.

[0063] Comparative Example 1

[0064] The difference from Example 1 is that: after 30°SR and 90°SR pulps are mixed and sieved at a ratio of 7:3, the pulps retained by 30 mesh and 50 mesh are taken and 0.16g (accounting for 6.88% of the mass of the base paper) of aramid nanofibers are mixed for papermaking, and the rest of the processes and procedures are the same as those in Example 1. The performance parameters of the cellulose insulating paper prepared in Comparative Example 1 are: thickness of 78 μm, tensile strength of 5.53 kN / m, tear strength of 967 mN, folding endurance of 321 times, breakdown voltage of 0.77 kV, breakdown strength of 9.17 kV / mm; the degree of polymerization of cellulose insulating paper impregnated with oil at 0d is 1002, and the degree of polymerization of cellulose insulating paper impregnated with oil at 25d is 206; the breakdown strength of cellulose insulating paper impregnated with oil at 0d is 15.33 kV / mm, and the breakdown strength of cellulose insulating paper impregnated with oil at 25d is 8.42 kV / mm.

[0065] Comparative Example 2

[0066] The difference from Example 1 is that 30°SR and 90°SR are mixed and sieved in the ratio of 8:2 to obtain 30 mesh and 100 mesh interception slurry and 0.3g (accounting for 12.62% of the base paper mass) of aramid nanofiber mixed papermaking, and the rest of the processes and procedures are the same as those in Example 1. The performance parameters of the cellulose insulating paper prepared in Comparative Example 2 are as follows: thickness is 78 μm, tensile strength is 5.35 kN / m, tear strength is 932 mN, folding endurance is 328 times, breakdown voltage is 0.69 kV, breakdown strength is 9.87 kV / mm; the degree of polymerization of cellulose insulating paper impregnated with oil for 0d is 1001, and the degree of polymerization of cellulose insulating paper impregnated with oil for 25d is 201; the breakdown strength of cellulose insulating paper impregnated with oil for 0d is 16.05 kV / mm, and the breakdown strength of cellulose insulating paper impregnated with oil for 25d is 8.78 kV / mm.

[0067] Comparative Example 3

[0068] The difference from Example 1 is that 40°SR and 80°SR are mixed and sieved according to 7:3 to take 30 mesh, 50 mesh and 100 mesh to intercept the slurry and weigh 0.04g (accounting for 2.66% of the base paper mass) of aramid nanofiber mixed papermaking, and the rest of the process and flow are the same as Example 1. The performance parameters of the cellulose insulating paper prepared in Comparative Example 3 are: thickness of 78μm, tensile strength of 5.63kN / m, tear strength of 985mN, folding endurance of 457 times, breakdown voltage of 0.91kV, breakdown strength of 10.01kV / mm; the degree of polymerization of cellulose insulating paper impregnated with oil for 0d is 1003, and the degree of polymerization of cellulose insulating paper impregnated with oil for 25d is 203; the breakdown strength of cellulose insulating paper impregnated with oil for 0d is 15.67kV / mm, and the breakdown strength of cellulose insulating paper impregnated with oil for 25d is 8.56kV / mm.

[0069] Comparative Example 4

[0070] The difference from Example 1 is that 55°SR slurry is used for papermaking, and the rest of the processes and procedures are the same as those of Example 1. The performance parameters of the cellulose insulating paper prepared in Comparative Example 4 are as follows: thickness is 78 μm, tensile strength is 4.43 kN / m, tear strength is 865 mN, folding endurance is 121 times, breakdown voltage is 0.67 kV, and breakdown strength is 8.67 kV / mm. The degree of polymerization of cellulose insulating paper impregnated with oil at 0d is 1089, and the degree of polymerization of cellulose insulating paper impregnated with oil at 25d is 108; the breakdown strength of cellulose insulating paper impregnated with oil at 0d is 8.45 kV / mm, and the breakdown strength of cellulose insulating paper impregnated with oil at 25d is 4.78 kV / mm.

[0071] Comparative Example 5

[0072] The difference from Example 1 is that 45°SR slurry is used for papermaking, and the rest of the processes and procedures are the same as those in Example 1. The performance parameters of the cellulose insulating paper prepared in Comparative Example 5 are as follows: thickness is 78 μm, tensile strength is 4.32 kN / m, tear strength is 876 mN, folding endurance is 131 times, breakdown voltage is 0.71 kV, and breakdown strength is 8.97 kV / mm; the degree of polymerization of cellulose insulating paper impregnated with oil for 0d is 1089, and the degree of polymerization of cellulose insulating paper impregnated with oil for 25d is 103; the breakdown strength of cellulose insulating paper impregnated with oil for 0d is 8.97 kV / mm, and the breakdown strength of cellulose insulating paper impregnated with oil for 25d is 5.12 kV / mm.

[0073] Comparative Example 6

[0074] The difference from Example 1 is that 65°SR slurry is used instead of papermaking, and the rest of the processes and procedures are the same as Example 1. The performance parameters of the cellulose insulating paper obtained in Comparative Example 6 are as follows: thickness is 78 μm, tensile strength is 4.09 kN / m, tear strength is 765 mN, folding endurance is 118 times, breakdown voltage is 0.68 kV, and breakdown strength is 8.77 kV / mm; the degree of polymerization of cellulose insulating paper impregnated with oil for 0d is 1089, and the degree of polymerization of cellulose insulating paper impregnated with oil for 25d is 101; the breakdown strength of cellulose insulating paper impregnated with oil for 0d is 9.12 kV / mm, and the breakdown strength of cellulose insulating paper impregnated with oil for 25d is 5.84 kV / mm.

[0075] Comparative Example 7

[0076] The difference from Example 1 is that the calendering process is eliminated in the process, and the other processes and processes are the same as Example 1. The performance parameters of the cellulose insulation paper prepared in Comparative Example 7 are as follows: thickness is 110 μm, tensile strength is 4.67 kN / m, tear strength is 634 mN, folding endurance is 571 times, breakdown voltage is 0.65 kV, breakdown strength is 8.56 kV / mm; the degree of polymerization of cellulose insulation paper impregnated with oil for 0d is 1019, and the degree of polymerization of cellulose insulation paper impregnated with oil for 25d is 175; the breakdown strength of cellulose insulation paper impregnated with oil for 0d is 14.68 kV / mm, and the breakdown strength of cellulose insulation paper impregnated with oil for 25d is 7.42 kV / mm.

[0077] Comparative Example 8

[0078] The difference from Example 1 is that no pulp purification treatment was performed. The ash content of the pulp raw material was 0.43% (≤0.25%) and the sodium ion content in the ash was 53.1 mg·kg -1 (≤30mg·kg -1 ) have exceeded the standard and have no paper value.

[0079] In comparative examples 1, 2, and 3, the tensile strength, folding resistance, and tear resistance of cellulose insulating paper before oil immersion all decreased with the changes in beating degree, fiber mixing ratio, and aramid nanofiber content, and they were all less than the strength of cellulose insulating paper in the embodiment. After oil immersion, the breakdown strength of cellulose insulating paper at 0d decreased from 15.68kV / mm to 8.58kV / mm at 25d. The results show that under high-temperature aerobic working conditions, fine fibers of cellulose insulating paper will be degraded first, and the water produced by them will aggravate the degradation of long fibers, reduce the length of cellulose macromolecular chains, and the mechanical properties of cellulose insulating paper will be more easily broken down after the decrease. After cellulose insulating paper is soaked in oil, its degree of polymerization at 0d is around 1100 on average, and the degree of polymerization at 25d is around 200. The results show that under long-term high-temperature aerobic working conditions, the degree of aging of cellulose insulating paper is serious, and the service life of cellulose insulating paper enters the late stage. Adjustments need to be made according to actual conditions to ensure the normal use of the transformer, otherwise it will be dangerous. In Comparative Examples 4, 5, and 6, cellulose insulating paper is made from a pulp with a beating degree. Compared with the cellulose insulating paper made from a mixture of pulps with two beating degrees, its mechanical properties are greatly reduced. After oil immersion, the degree of polymerization of the cellulose insulating paper decreases from 1100 at 0d to around 100 at 25d. The results show that the aging degree of cellulose insulating paper becomes more serious with the increase of operating time. The life of cellulose insulating paper enters the end and cannot be used any more. New cellulose insulating paper needs to be replaced to ensure the safe operation of the transformer. Compared with the cellulose insulating paper with calendering, the cellulose insulating paper without calendering in Comparative Example 7 has an increased thickness and a decreased tightness. The calendering treatment helps to improve the tightness and flatness of the paper, thereby improving its overall performance. After 25d of oil immersion, the degree of polymerization of the cellulose insulating paper is less than 180, the aging degree is very serious, the breakdown strength is significantly reduced, and the life enters the late stage. It needs to be decided according to the actual situation, otherwise it will be dangerous. In Comparative Example 8, the pulp for making cellulose insulating paper was not purified, and the detected chemical component indexes failed to meet the indexes of cellulose insulating paper used in ultra-high voltage transformers, making it difficult to proceed with subsequent steps.

[0080] In summary, the long fibers intercepted by a small mesh screen are used, and the fine fibers screened out from the pulp are replaced by aramid nanofibers. The two are mixed in a certain proportion for papermaking. The cellulose insulating paper obtained after calendering has better insulation performance and breakdown strength than the cellulose insulating paper in the comparative example. After aging, the polymerization degree of the former is significantly higher than that of the latter. This method not only ensures the good mechanical properties of the cellulose insulating paper, but also slows down the aging rate of the polymerization degree of the paper-made cellulose insulating paper, effectively prolonging the service life of the cellulose insulating paper, making the cellulose insulating paper more resistant to aging. By comparing the results of the embodiments and comparative examples, we can clearly understand the effects of different conditions on the performance of cellulose insulating paper, as well as the important role of aramid nanofibers in improving the performance of insulating paper.

[0081] The present invention uses specific examples to illustrate the principles and implementation methods of the present invention. The above-mentioned embodiments are only preferred implementation methods of this patent and are only used to help understand the method and core ideas of the present invention. At the same time, for those skilled in the art, according to the ideas of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A method for preparing aging-resistant cellulose insulating paper, characterized in that: The following steps are involved: (1) Pre-treating the wood pulp board: soaking the wood pulp board in deionized water to loosen it; (2) subjecting the pretreated pulp to mechanical refining to different degrees, and mixing the pulp in proportion according to the difference in the degree of beating to obtain a mixed pulp; (3) subjecting the mixed slurry to purification treatments: hydrochloric acid treatment and magnesium acetate treatment; (4) mechanically screening the treated pulp to remove fine fibers in the pulp and obtain a good pulp free of fine fibers; (5) replacing the cellulose fine component with an equal amount of aramid nanofibers to obtain a mixed pulp containing aramid nanofibers; (6) debonding the obtained mixed pulp and obtaining cellulose base paper by wet forming technology; (7) Calendering the obtained cellulose base paper to obtain cellulose insulation paper.

2. The preparation method according to claim 1, characterized in that: The wood pulp board includes softwood / hardwood kraft pulp, softwood / hardwood sulfite pulp, etc., and the cellulose polymerization degree is 1000-1900.

3. The preparation method according to claim 1, characterized in that: The mechanical refining has a refining speed of 5000-20000 r (revolutions), a pulp concentration of 5-20%, a refining gap of 0-4 mm, and a pulp beating degree of 40-95° SR.

4. The preparation method according to claim 1, characterized in that: The mixed slurry is compounded according to the beating degree, wherein the low beating degree ranges from 30 to 65°SR, the high beating degree ranges from 70 to 95°SR, and the mixing ratio of the two is 5:5 to 9:

1.

5. The preparation method according to claim 1, characterized in that: The concentration of the acid-treated slurry is 0.5-5%, and the concentration of the hydrochloric acid is 0.5-3%; the concentration of the magnesium salt-treated slurry is 0.5-5%, and the concentration of the magnesium acetate is 1-5%.

6. The preparation method according to claim 1, characterized in that: The mesh number of the mechanical screening is 20 to 200 meshes.

7. The preparation method according to claim 1, characterized in that: The nanofiber is aramid nanofiber with a diameter of 20-200 nm and an aspect ratio of 500-2000.

8. The preparation method according to claim 1, characterized in that: The content of the replaced fine fibers is 1-20% of the mass of the cellulose insulation paper, that is, the content of the aramid nanofibers is 1-20% of the mass of the finished paper.

9. The preparation method according to claim 1, characterized in that: The roller calendering temperature is 50-100° C., the hot pressing roller speed is 0.5-10 m / min, and the calendering line pressure is 5-70 N / mm.

Citation Information

Patent Citations

  • Method for preparing electrical insulating papers containing broadleaf wood fibers

    CN104863022A

  • Micro-nanocellulose fiber / aramid composite insulating paper and preparation method thereof

    CN109024094A

  • Breakdown-resistant composite electrolytic capacitor paper and production method thereof

    CN109722945A

  • High-mechanical-strength aramid insulating paper as well as preparation method and application thereof

    CN112663382A

  • Preparation method of cellulose / aramid nanofiber in-situ composite fiber

    CN113278172A

Cited By

  • Method for Manufacturing Insulating Paper based on Kraft Pulp

    KR102989371B1